SYNTHESIS AND CHARACTERIZATION OF CESIUM SILICATE TO DETERMINE ITS DETAILED PROPERTIES AS CHEMISORBED ONTO STRUCTURAL MATERIALS OF LIGHT WATER REACTOR DURING SEVERE ACCIDENT CONDITIONS - I Wayan Ngarayana (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2023)
Cesium chemisorption phenomenon strongly contributes to the source terms transport during light water nuclear reactor accidents. Large amounts of cesium silicates are identified to be chemisorbed onto structure material, reduce cesium volatility, and affect the late release and re-vaporization phenomena. Although it has been studied for a long time, several characteristics of these compounds are still under discussion. In this study, Cs2SiO3, Cs2Si2O5, and Cs2Si4O9 were synthesized through the solid-state method and the results have been confirmed using X-Ray Diffraction (XRD) measurement. Furthermore, their crystal structures have been refined based on the XRD analysis. The crystal structure refinement of these compounds proves the previous studies, but with minor distinctions in the lattice parameters. XRD patterns changing over time when measured in the open-air environment also show that Cs2Si4O9 is the most stable species among other cesium silicate species. This indicates that the chemisorbed Cs-Si-O compound onto the structural material as identified by previous studies is most likely Cs2Si4O9 rather than Cs2SiO3 or Cs2Si2O5. Therefore, detailed Cs2Si4O9 identification including its thermodynamic properties characterization could be very useful to enhance the database that is being built to improve current source terms transport codes.